CORRECTION OF METABOLIC VIOLATIONS AND ENERHO- DEFITSIT AT CHILDREN PATIENT WITH BRONCHIAL ASTHMA WITH DISFUNCTION OF SERTSEVO-SOUDINNOI SYSTEM - Фофанова, О. В.; Павликівська, Б. М.; Юрцева, А. П.; Боднар, О. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Work is based on the results of examination of 73 children with asthma, who have dysfunction of the cardiovascular system, which were shown violation of repolarization processes, sinus brady- and tachycardia, incomplete Right Bundle Branch Block (RBBB). In biochemical studies were found activation of lipid peroxidation (LPO), increased oxidative modification of proteins (OMP), decline in antioxidant defense, the level of ATP and pyruvate, increasing of lactate. Inclusion in the complex therapy drugs "Cardonat" and "Pikovit Plus" improves the basic parameters of the cardiovascular system function, promotes normalization of antioxidant protection and energy metabolism.